2013
DOI: 10.1016/j.watres.2013.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Retention of pesticide Endosulfan by nanofiltration: Influence of organic matter–pesticide complexation and solute–membrane interactions

Abstract: Nanofiltration (NF) is a well-established process used in drinking water production to effectively remove Natural Organic Matter (NOM) and organic micropollutants. The presence of NOM has been shown to have contrasting results on micropollutant retention by NF membranes and removal mechanisms are to date poorly understood. The permeate water quality can therefore vary during operation and its decrease would be an undesired outcome for potable water treatment. It is hence important to establish the mechanisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…3(a) and 3(b), respectively. Similar findings for Fe removal has previously been reported by Jusoh et al [7] and De Munari et al [19]. Regarding to Mn 2+ ions, De Munari and Schafer [14] reported that PA-NF membrane has achieved more than 95% of rejection at pH 7.…”
Section: Rejectionsupporting
confidence: 88%
See 1 more Smart Citation
“…3(a) and 3(b), respectively. Similar findings for Fe removal has previously been reported by Jusoh et al [7] and De Munari et al [19]. Regarding to Mn 2+ ions, De Munari and Schafer [14] reported that PA-NF membrane has achieved more than 95% of rejection at pH 7.…”
Section: Rejectionsupporting
confidence: 88%
“…Lower rejection of Mn could be attributed solely to the electrostactic effect interaction between membrane material and Mn 2+ ions [18]. The isoelectric point (IEP) of PA-NF is in the range of 6 to 8 as reported by De Munari et al [19]. This membrane is characterized as an amphoteric membrane whereby it is positively charged in solution less than pH 6 and negatively charged in solution more than pH 8.…”
Section: Permeate Qualitymentioning
confidence: 72%
“…When HA is added, retention of TCS is influenced by its association with HA retained on the surface of membrane and this increases retention [15]. De Munaria et al [12] indicated that the formation of solute-HA complexes and an increase in MWCO of NF membrane are the mechanisms involved. The formation of solute-HA complexes cause an increase in solute retention, while the interactions between HA and the membrane causes a decrease in solute retention [12].…”
Section: Tcs Rejection: the Role Of Hamentioning
confidence: 99%
“…Nanofiltration (NF) has been considered as an effective and feasible technique for the production of high quality water from various water sources containing micropollutants [5]. However, there are contrasting results regarding the removals of micropollutants by NF [6][7][8][9][10][11][12]. Some researchers have attributed the contradictory results to the different types of micropollutants, membranes and organic matter used and to the complexity of the retention mechanisms [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation